Pengetahuan Ibu Rumah Tangga Terhadap Pentingnya Gizi Dalam Tumbuh Kembang Anak Di Desa Latonro Kecamatan Cenrana - Sakiah Sakiah; Hamdiana Hamdiana; Sakinah Amir (Journal of Innovative and Creativity, 2026)
Child malnutrition remains a critical issue in rural Indonesia, particularly in isolated areas like Desa Latonro, where limited access and low maternal literacy hinder balanced nutrition for child growth. This study aims to analyze housewives' knowledge of nutrition's importance in child development, identify influencing factors, and barriers to implementation. Employing a qualitative descriptive phenomenology approach, data were collected via semi-structured in-depth interviews, participatory observation, and secondary documents from July-August 2025. The population comprised housewives aged 19-45 with toddlers in Desa Latonro; purposive sampling yielded 20 informants until saturation. Instruments included interview guides; thematic analysis followed Braun and Clarke (2022) using NVivo, validated by triangulation. Results indicate varied knowledge levels (13/20 aware of basics like carbohydrates, proteins, vitamins), simple feeding patterns (rice with fish/eggs), and barriers including economic constraints, child preferences, and limited information access. In conclusion, maternal nutrition literacy requires community-based interventions leveraging local seafood resources.